2016
DOI: 10.3390/membranes6030036
|View full text |Cite
|
Sign up to set email alerts
|

Biochip for the Detection of Bacillus anthracis Lethal Factor and Therapeutic Agents against Anthrax Toxins

Abstract: Tethered lipid bilayer membranes (tBLMs) have been used in many applications, including biosensing and membrane protein structure studies. This report describes a biosensor for anthrax toxins that was fabricated through the self-assembly of a tBLM with B. anthracis protective antigen ion channels that are both the recognition element and electrochemical transducer. We characterize the sensor and its properties with electrochemical impedance spectroscopy and surface plasmon resonance. The sensor shows a sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
(140 reference statements)
1
5
0
Order By: Relevance
“…However, unlike what was found previously for other toxins, and verified here for anthrax PA (Fig. S1) ( 24, 25 ), CDTb did not bind lipid bilayers or form pores in membrane-like vesicles upon lowering pH to acidic values.…”
Section: Main Textsupporting
confidence: 69%
“…However, unlike what was found previously for other toxins, and verified here for anthrax PA (Fig. S1) ( 24, 25 ), CDTb did not bind lipid bilayers or form pores in membrane-like vesicles upon lowering pH to acidic values.…”
Section: Main Textsupporting
confidence: 69%
“…It is often easier to detect proteins through an interaction outside the pore. One can take advantage of the natural binding affinity of AB toxins, such as the anthrax toxins, to devise a binding assay sensor . Rostovsteva and colleagues used a co‐localization assay to identify a likely sensor for the tubulin, which has disordered c‐terminal tails (CTT) that differ between isotypes.…”
Section: Protein Sensingmentioning
confidence: 99%
“…PA63 has been proven useful for both the detection of two other anthrax toxins (Lethal Factor and Edema Factor) with high sensitivity (ca. 40 pM) and screening for therapeutic agents against them. , Many studies have demonstrated reversible interactions between the N-terminus of Lethal Factor and Edema factor, but under certain conditions the interaction becomes irreversible …”
Section: Detection and Characterization Of Small Moleculesmentioning
confidence: 99%
“…40 pM) and screening for therapeutic agents against them. 87,88 Many studies have demonstrated reversible interactions between the N-terminus of Lethal Factor and Edema factor, 89−91 but under certain conditions the interaction becomes irreversible. 86 The MspA channel had to be modified for DNA sequencing applications (described above) because the native channel produces spontaneous ionic current blockades in the absence of single-stranded DNA, which would confound the characterization of nucleic acids.…”
Section: Acs Sensorsmentioning
confidence: 99%